Membrane bridging by Munc13-1 is crucial for neurotransmitter release - Quade, Bradley (eLife, 2019)
Munc13-1 plays a crucial role in neurotransmitter release. We recently proposed that the C-terminal region encompassing the C(1), C(2)B, MUN and C(2)C domains of Munc13-1 (C(1)C(2)BMUNC(2)C) bridges the synaptic vesicle and plasma membranes through interactions involving the C(2)C domain and the C(1)-C(2)B region. However, the physiological relevance of this model has not been demonstrated. Here we show that C(1)C(2)BMUNC(2)C bridges membranes through opposite ends of its elongated structure. Mutations in putative membrane-binding sites of the C(2)C domain disrupt the ability of C(1)C(2)BMUNC(2)C to bridge liposomes and to mediate liposome fusion in vitro. These mutations lead to corresponding disruptive effects on synaptic vesicle docking, priming, and Ca(2+)-triggered neurotransmitter release in mouse neurons. Remarkably, these effects include an almost complete abrogation of release by a single residue substitution in this 200 kDa protein. These results show that bridging the synaptic vesicle and plasma membranes is a central function of Munc13-1.